Structural and optical properties of Eu-doped ZnO epitaxial thin films grown by pulsed-laser deposition - Wei-Lun Wei; Chun-Yen Lin; Tzu-Chi Huang; Yi-Chen Li; Yu-Hao Wu; Chien-Yu Lee; Bo-Yi Chen; Gung-Chian Yin; Mau-Tsu Tang; Wu-Ching Chou; Fang-Yuh Lo; Bi-Hsuan Lin (APL Materials)
Pulsed-laser deposition was utilized to fabricate Eu-doped ZnO epitaxial films on c-plane sapphire substrates with Eu concentrations ranging from 0.5 to 4.0 at. %. The structural properties were analyzed using x-ray diffraction surface normal radial scans and azimuthal cone scans, which confirmed the epitaxy of the film samples. Reciprocal space mapping was performed on ZnO(101̄1) to visualize the effect of Eu incorporation. X-ray fluorescence mapping confirmed the homogeneous distribution of Zn and Eu, and x-ray absorption near-edge structure spectra directly confirmed the trivalent state of Eu ions. The optical properties were assessed using temperature-dependent photoluminescence (PL). Various defects were identified. With increasing Eu dopant concentration, PL emissions from defects and the Eu 4f-intraband transitions gradually became the predominant features in the PL spectra at low temperatures. Furthermore, PL analysis suggested that Eu ions substituted Zn, occupying sites with lower C3v symmetry due to the distortion caused by Eu incorporation.